Nondermatomal somatosensory deficits in chronic pain are associated with cerebral grey matter changes. (3rd April 2017) - Riederer, Franz; Landmann, Gunther; Gantenbein, Andreas R.; Stockinger, Lenka; Egloff, Niklaus; Sprott, Haiko; Schleinzer, Wolfgang; Pirrotta, Roberto; Dumat, Wolfgang; Luechinger, Roger; Baumgartner, Christoph; Kollias, Spyridon; et al.
Abstract: Objectives : Widespread sensory deficits occur in 20–40% of chronic pain patients on the side of pain, independent of pain aetiology, and are known as nondermatomal sensory deficits (NDSDs). NDSDs can occur in absence of central or peripheral nervous system lesions. We hypothesised that NDSDs were associated with cerebral grey matter changes in the sensory system and in pain processing regions, detectable with voxel-based morphometry. Methods : Twenty-five patients with NDSDs, 23 patients without NDSDs ("pain-only"), and 29 healthy controls were studied with high resolution structural MRI of the brain. A comprehensive clinical and psychiatric evaluation based on Diagnostic and Statistical Manual was performed in all patients. Results : Patients with NDSDs and "pain-only" did not differ concerning demographic data and psychiatric diagnoses, although anxiety scores (HADS-A) were higher in patients with NDSDs. In patients with NDSDs, grey matter increases were found in the right primary sensory cortex, thalamus, and bilaterally in lateral temporal regions and the hippocampus/fusiform gyrus. "Pain-only" patients showed a bilateral grey matter increase in the posterior insula and less pronounced changes in sensorimotor cortex. Conclusions : Dysfunctional sensory processing in patients with NDSDs is associated with complex changes in grey matter volume, involving the somatosensory system and temporal regions.